Analytical differentiation by computer using a Symmetrical List Processor - Lichtman, Barry Martin (Department of Computer Science, 2016)
The Symmetrical List Processor SLIP; developed by Professor Joseph Weizenbaum of MIT, was implemented with considerable modifications and additions on the University of Cape Town computer. A package to perform automated analytical differentiation (DERIV) was developed using SLIP. Basic simplification techniques as well as convenient input and output routines were included. The package was tested extensively and a rough comparison drawn with the abilities of various computer languages and programs which include the same facility as TIERIV.